Knowledge, attitudes, and willingness of bipolar disorder patients toward electroconvulsive therapy: a cross-sectional study - Lin Zhou; Lin Zhou; Xinmeng Qi; Liuliu Xu; Liuliu Xu; Xinrong Duanmu; Ke Wang; Kai Liu; Yue Zhang (Frontiers in Public Health, 2025)
ObjectiveThis research aims to explore the levels of knowledge, attitudes, and willingness (KAW) of patients with bipolar disorder (BD) regarding electroconvulsive therapy (ECT).MethodsA cross-sectional survey was conducted in Nanjing from April 10 to November 3, 2024, using a validated questionnaire [Cronbach's α = 0.936, Kaiser–Meyer–Olkin (KMO) = 0.917]. Participants completed structured items assessing knowledge, attitudes, and willingness toward ECT. Data analysis involved descriptive statistics, non-parametric tests, Spearman correlation, multivariate logistic regression, and structural equation modeling (SEM).ResultsThe study successfully enrolled 479 participants. Of these, 282 participants (58.87%) were female. One hundred and sixty seven respondents (34.86%) had previously undergone ECT. The mean knowledge, attitude, and willingness scores were 5.57 ± 4.84 (possible range: 0–16), 29.08 ± 6.21 (possible range: 9–45), and 21.49 ± 5.14 (possible range: 6–30), respectively. SEM analysis showed that electroconvulsive therapy (β = −0.377, P = 0.014), years of BD (β = 0.196, P = 0.014) had direct effects on knowledge. Knowledge (β = 0.526, P = 0.023) directly affected attitude. Meanwhile, electroconvulsive therapy (β = −0.198, P = 0.013) and years of BD (β = 0.103, P = 0.016) indirectly affected attitude. Knowledge (β = 0.107, P = 0.018), attitude (β = 0.674, P = 0.009), and gender (β = 0.104, P = 0.020) directly affected willingness. Knowledge (β = 0.355, P = 0.011), electroconvulsive therapy (β = −0.174, P = 0.015), and years of BD (β = 0.090, P = 0.020) indirectly affected willingness.ConclusionThe study found that bipolar disorder patients generally lack knowledge and hold negative attitudes but demonstrate a relatively high willingness to accept ECT treatment. Targeted educational programs are recommended to improve understanding, shift attitudes, and enhance acceptance of this treatment in clinical willingness.